Nonprecious Bimetallic Sites Coordinated on N‐Doped Carbons with Efficient and Durable Catalytic Activity for Oxygen Reduction - Yuan, Shan; Cui, Li‐Li; Dou, Zhiyu; Ge, Xin; He, Xingquan; Zhang, Wei; Asefa, Tewodros (Small (Weinheim an der Bergstrasse, Germany), 2020)
Developing efficient, inexpensive, and durable electrocatalysts for the oxygen reduction reaction (ORR) is important for the large‐scale commercialization of fuel cells and metal–air batteries. Herein, a hierarchically porous bimetallic Fe/Co single‐atom‐coordinated N‐doped carbon (Fe/Co‐Nx‐C) electrocatalyst for ORR is synthesized from Fe/Co‐coordinated polyporphyrin using silica template‐assisted and silica‐protection synthetic strategies. In the synthesis, first silica nanoparticles‐embedded, silica‐protected Fe/Co‐polyporphyrin is prepared. It is then pyrolyzed and treated with acidic solution. The resulting Fe/Co‐Nx‐C material has a large specific surface area, large electrochemically active surface area, good conductivity, and catalytically active Fe/Co‐Nx sites. The material exhibits a very good electrocatalytic activity for the ORR in alkaline media, with a half‐wave potential of 0.86 V versus reversible hydrogen electrode, which is better than that of Pt/C (20 wt%). Furthermore, it shows an outstanding operational stability and durability during the reaction. A zinc–air battery (ZAB) assembled using Fe/Co‐Nx‐C as an air‐cathode electrocatalyst gives a high peak power density (152.0 mW cm−2) and shows a good recovery property. Furthermore, the performance of the battery is better than a corresponding ZAB containing Pt/C as an electrocatalyst. The work also demonstrates a synthetic route to a highly active, stable, and scalable single‐atom electrocatalyst for ORR in ZABs. An efficient oxygen reduction reaction (ORR) electrocatalyst composed of bimetallic (Fe and Co) single atoms coordinated with N‐doped carbon (Fe/Co‐Nx‐C) is synthesized with silica template‐assisted and mesoporous silica‐protection synthetic methods. Compared with Pt/C, Fe/Co‐Nx‐C shows a better electrocatalytic activity, stability, and durability for ORR in zinc–air batteries.